Ecology as a Tool to Assist Conservation of a Rare and Endemic Mediterranean Plantago Species - Serrano, Helena Cristina; Pinto, Manuel João; Branquinho, Cristina; Martins-Loução, Maria Amélia (Frontiers in Ecology and Evolution, 2021)
Reviewing the ecological studies on the endangered endemic Plantago almogravensis Franco, an Al hyper-accumulator plant, and combining these with morphological, physiological, biochemical and molecular data, a significant knowledge on the limiting factors that cause its narrow geographical distribution and rarity status is achieved, which can contribute for suited conservation guidelines. Emphasis was given on: (i) major factors limiting P. almogravensis' ecological niche (biotic and abiotic); (ii) phases of the life cycle and population dynamics; (iii) and phylogenetically close taxa (P. subulata aggregate); to fill knowledge gaps in the uniqueness of P. almogravensis ecology, its phylogeny and conservation status. The identification of relevant ecological data and using plant functional (morphological and physiological) traits, as well as genetic attributes, substantiates into a powerful tool to guide protection and conservation measures, usable towards this and other endangered hyper-accumulator plant species. The knowledge of the limitations of this strongly narrowed-distributed plant, allows for better conservation measures' design and to guide value and investment strategies, to secure the species' current area (habitat conservation and reclamation) and/or direct the expansion of the existing population (assisting in populational densification, and colonization) and/or grant ex-situ conservation (genetic resources conservation).